Experience from the DARPA urban challenge - Hinchey, Mike (Springer London, 2012)
Experience from the DARPA Urban Challenge provides details of the types of systems, software and processes that were used to develop the complex unmanned vehicles that participated in the DARPA Urban Challenge. The vehicle developers explain how autonomous vehicle software in this race was designed and implemented. The chapters range from system and software architecture, navigation, path planning, steering, perception, engineering autonomous systems, and testing and performance evaluation. This book is based on papers from entrants in the Urban Challenge. The content is broken into five parts: an introduction to the DARPA Urban Challenge; systems and software architectures; navigation; control and sensors; and development and test. Experience from the DARPA Urban Challenge provides graduate students in robotics and engineering professionals with an insight into multiple ways of approaching the development of autonomous vehicles.